Using Floating Bike Data to Determine Cyclist Exposure to Poor Air Quality - Caulfield, Brian (My University, 2021)
Introduction: The World Health Organisation (WHO) claims that 9 out of 10 people breath air containing high levels of pollutants, while air pollution itself is responsible for around 7 million premature deaths every year (WHO, 2014). This paper aims to determine the health impacts of such air pollutants on the cyclist population of Dublin City through the use of floating bike data and emission modelling software. Methods: Through the use of COPERT Street Level vehicle emissions are estimated and Operational Street Pollution Model, NO2 and PM2.5 quantities and NO2 concentrations were modelled on four separate roads that had been identified as some of the busiest cycle corridors in Dublin city through the use of floating bike data. The NO2 quantities were then used to estimate the associated economic impact and concentrations were used to estimate the health impact on the exposed cyclist population using the WHO Burden of Disease (BOD) method. Results: The results suggested that as much as 18.4 million Euro worth of damage is done each year on just one of the four roads modelled in this research, indicating that the total damage being done in Dublin city could reach into the billions a year, as this is only considering NO2 pollution on one road. In terms of the BOD results, it was calculated that as many as 37 premature deaths could be caused due to exposure to the NO2 concentrations modelled, resulting in 412 Years of Life Lost (YLL). Conclusions: Through the use of modelled scenarios where the fleet configuration changes, the findings of this study create an argument that significant measures need to be taken to reduce the air pollution levels in Dublin in order to prevent the needless infliction of disease and premature death on the relevant exposed population.
PUBLISHED
Keywords: Smart & Sustainable Planet; CYCLING; transport; Transport